2023
DOI: 10.1080/19382014.2023.2252855
|View full text |Cite
|
Sign up to set email alerts
|

Beta cell primary cilia mediate somatostatin responsiveness via SSTR3

Samantha E. Adamson,
Zipeng A. Li,
Jing W. Hughes

Abstract: Somatostatin is a paracrine modulator of insulin secretion and beta cell function with pleotropic effects on glucose homeostasis. The mechanism of somatostatin-mediated communication between delta and beta cells is not well-understood, which we address in this study via the ciliary somatostatin receptor 3 (SSTR3). Primary cilia are membrane organelles that act as signaling hubs in islets by virtue of their subcellular location and enrichment in signaling proteins such as G-protein coupled receptors (GPCRs). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 63 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Beta cell cilia have been shown to be involved in GABA signaling (54). Furthermore, they express the insulin (31), somatostatin (55; 56), and various G protein-coupled receptors (46). If some of these pathways are especially prominent at cilia-islet cell connections remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Beta cell cilia have been shown to be involved in GABA signaling (54). Furthermore, they express the insulin (31), somatostatin (55; 56), and various G protein-coupled receptors (46). If some of these pathways are especially prominent at cilia-islet cell connections remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Using beta cells lacking cilia or with a defective cilia receptor trafficking machinery, it has been shown that some, if not all, of the effects of both SSTR3 and FFAR4 on insulin secretion modulation are exerted via cilia-localised receptors [ 4 , 6 8 , 17 ]. Many receptors or receptor families, for example SSTRs, are also present on the plasma membrane, suggesting that some ligands may trigger parallel canonical and ciliary pathways, which may increase the information content carried by a given ligand.…”
Section: Primary Cilia As Sensors Of the Islet Microenvironmentmentioning
confidence: 99%
“…The primary cilium is also a unique cAMP compartment that contains both adenylate cyclases (ACs) and phosphodiesterases (PDEs) as well as PKA, and several of these are directly controlled by Ca 2+ /calmodulin, which might enable local crosstalk between the Ca 2+ and cAMP pathways [ 31 ]. Beta cell primary cilia contain both AC3 and AC5/6, and activation of GPR120 can stimulate ciliary cAMP formation [ 4 , 8 , 17 ]. Given the presence of both G s - and G i -coupled receptors on the beta cell cilia (Fig.…”
Section: Coupling Ciliary Receptors To Downstream Signalling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations